FAKTOR RISIKO DENGAN ANGKA KEJADIAN POST OPERATIVE NAUSEA AND VOMITING PADA PASIEN YANG DILAKUKAN ANESTESI SPINAL DI RSUD DR. M. HAULUSSY AMBON DAN RS BHAYANGKARA AMBON TAHUN 2022 - Prily G Lekatompessy; Cokorda I.A. Devi; Presli Glovrig Siahaya; Is Ikhsan Hataul (PAMERI, 2022)
Introduction: Postoperative Nausea and Vomiting (PONV) is a side effect that often occurs after anesthesia. PONV is associated with various factors, these factors are categorized into risk factors related to patient, surgery, and anesthesia. PONV can occur in men and women of all ages. Although it is not known for certain, smoking is believed to prevent the occurrence of PONV. In addition, prophylactic administration of ondansetron can also prevent the occurrence of PONV. Objective: This study aims to determine the relationship between risk factors and the incidence of PONV in patients undergoing spinal anesthesia at Dr. M. Haulussy Ambon and Bhayangkara Hospital Ambon in 2022. Methods: This study is an observational analytic study with a cross sectional approach which was conducted in February-March 2022 by using a total sampling technique of 43 patients who underwent lower abdominal surgery and underwent spinal anesthesia at Dr. Hospital. M. Haulussy Ambon and Bhayangkara Hospital Ambon. The instrument used is a questionnaire taken from the article “Simplified Postoperative Nausea and Vomiting Impact Scale for Audit and Post-Discharge Review in the British Journal of Anaesthesia” that has been modified. Data were analyzed using the Chi-Square test to determine the relationship between risk factors and the incidence of PONV in patients undergoing spinal anesthesia. Results: The results showed that there was a significant relationship between age (P=0.027), gender (P=0.008), smoking history (P=0.011), and history of ondansetron prophylaxis (P=0.005) with the incidence of PONV in patients after lower abdominal surgery. with spinal anesthesia. Conclusions: This study shows the importance of knowing the risk factors to be aware of the occurrence of PONV after lower abdominal surgery with spinal anesthesia at Dr. M. Haulussy Ambon and Bhayangkara Hospital Ambon.